A review of road models for vehicular control. Issue 6 (3rd June 2023) - Limebeer, D. J. N.; Warren, E.
Abstract : Over the last 25 years a number of road models have been developed for use in a variety of vehicular control problems. These models are important, because they dictate the force-generating capabilities of the tyres, as well as constrain the movement of the vehicle itself. Early road models used two-dimensional (2D) 'flat road' representations, the advantages and deficiencies of which are well understood. Once it became apparent that three-dimensional effects can be important in limit-performance studies, ribbon-based three-dimensional (3D) road models were developed. The large lateral camber variations on highly-banked NASCAR tracks highlighted deficiencies in ribbon-based road representations that required correction. Upgraded models addressing these deficiencies were only developed recently. The purpose of this paper is to review and compare a number of road models – particularly those developed for use in racing studies. Comparative computed results are provided that hight some of the similarities and differences between these models.